The Postcolonial Experience: Socio-Cultural Dislocation in Things Fall Apart - Kandel, Bhanu Bhakta Sharma (AWADHARANA, 2025)
Disintegration is usually caused by imperialistic totalitarian imposition in a political sense. The present study is an examination of Chinua Achebe's Things Fall Apart, his first novel, published in 1958. From its date of publication, the novel has extensively attracted many critics, as Chinua Achebe's ideas have caused some consternation due to their polemical nature. Achebe’s writings are primarily based on traditional oral literature and on the present and rapidly changing society. Unlike some African writers struggling for acceptance among contemporary English-language novelists, Achebe has been able to avoid imitating trends in English literature. This paper will explore how indigenous people suffered from cultural imperialism, which is the cause of the disintegration of society. Achebe's portrayal of culture in his fictional universe reflects the prevailing socio-cultural context of the period. Critical insights from post-colonial studies have been employed to interpret the novel, and MLA has been utilized to present references. The study's findings in this article are that Things Fall Apart presents the struggle between change and tradition, which leads to the protagonist's downfall, specifically the suspension of social hierarchy in Igbo society, as white people imperialize Nigeria in the name of religious missionaries.